The Tanah Air has always been cosmopolitan - Mohd Noor Merican, Ahmad Murad (Melaka Hari Ini Sdn. Bhd., 2020)
The Malays have two sets of narratives in encounters with the West – one is actual, the other mythical/ metaphysical. Melaka was one of the earliest places of encounters, in both sense of the word, producing the Ferringhis and Rum (Rome).